Randomized Trial of Individualized Texting for Adherence Building (iTAB) Plus Motivational Interviewing for PrEP Adherence in Transgender Individuals: The iM-PrEPT Study. (15th December 2022) - Morris, Sheldon R.; Jain, Sonia; Blumenthal, Jill; Bolan, Robert; Dubé, Michael P.; Henderson, Philip; Corado, Katya; Sun, Shelly; He, Feng; Chow, Karen; Burke, Leah; Anderson, Peter L.; et al.
Abstract : Background: Transgender and nonbinary individuals at risk for HIV may benefit from adherence support for pre-exposure prophylaxis. Methods: Between June 2017 and September 2020, 255 transgender and nonbinary individuals received daily oral tenofovir disoproxil fumarate/emtricitabine for 48 weeks randomized 1:1 to receive individualized Texting for Adherence Building (iTAB) or iTAB plus motivational interviewing (iTAB + MI) through phone for nonadherence. The primary end point was dried blood spot tenofovir diphosphate concentrations at weeks 12 and 48 (or last on-drug study visit) ≥1246 fmol/punch consistent with ≥7 doses/week (ie, near-perfect adherence). Secondary outcomes included dried blood spot tenofovir diphosphate concentrations ≥719 fmol/punch consistent with ≥4 doses/week (ie, adequate adherence) and self-reported adherence by daily text messages. Results: Adherence for the outcome ≥1246 fmol/punch and ≥719 fmol/punch, respectively, was 49.1% and 57.9% for transgender men, 37.7% and 47.2% for nonbinary individuals, and 31.0% and 44.1% for transgender women. No difference was seen in iTAB + MI compared with iTAB alone by drug levels except where it approached significance in transgender women for the outcome of ≥719 fmol/punch in the iTAB + MI group compared with iTAB only (52% versus 35.7%, P = 0.065). There was a significant difference in self-reported daily dose adherence in the iTAB + MI group compared with iTAB alone (57.9% of days versus 46.4%, P = 0.009). In transgender women, the mean percentage of daily doses taken was 58.5% with iTAB + MI and 37.3% with iTAB alone ( P < 0.001). Conclusions: In addition to automated approaches to adherence promotion, phone-based MI triggered by repeatedly missing doses may improve pre-exposure prophylaxis adherence among transgender women.